Conjugation of plasmid harboring blaNDM-1 in a clinical Providencia rettgeri strain through the formation of a fusion plasmid - Zhang, Meng; Yu, Yanhua; Wang, Qian; Chen, Ran; Wang, Yueling; Bai, Yuanyuan; Song, Zhen; Lu, Xinglun; Hao, Yingying (Frontiers in Microbiology, 2023)
Providencia rettgeri has recently gained increased importance owing to the New Delhi metallo-β-lactamase (NDM) and other β-lactamases produced by its clinical isolates. These enzymes reduce the efficiency of antimicrobial therapy. Herein, we reported the findings of whole-genome sequence analysis and a comprehensive pan-genome analysis performed on a multidrug-resistant P. rettgeri 18004577 clinical strain recovered from the urine of a hospitalized patient in Shandong, China, in 2018. rettgeri 18004577 was found to have a genome assembly size of 4.6 Mb with a G + C content of 41%, a circular plasmid p18004577_NDM of 273.3 Kb harboring an accessory multidrug-resistant region, and a circular, stable IncT plasmid p18004577_Rts of 146,.2 Kb. Additionally, various resistance genes were identified in its genome, including blaNDM-1, blaOXA-10, blaPER-4, aph(3′)-VI, ant(2′′)-Ia, ant(3′)-Ia, sul1, catB8, catA1, mph(E), and tet. Conjugation experiments and whole-genome sequencing revealed that the blaNDM-1 gene could be transferred to the transconjugant via the formation of pJ18004577_NDM, a novel hybrid plasmid. Based on the genetic comparison, the main possible formation process for pJ18004577_NDM was insertion of the [ΔISKox2-IS26-ΔISKox2]-aph(3’)-VI-blaNDM-1 translocatable unit module from p18004577_NDM into plasmid p18004577_Rts in the Russian doll insertion structure [ΔISKox2-IS26-ΔISKox2], which played a role similar to that of IS26 using the “ copy-in” route in the mobilization of [aph(3’)-VI]-blaNDM-1. The array, multiplicity and diversity of the resistance and virulence genes in this strain necessitate stringent infection control, antibiotic stewardship, and periodic resistance surveillance/monitoring policies to preempt further horizontal and vertical spread of the resistance genes. Roary analysis based on 30 P. rettgeri strains pan genome identified 415 core, 756 soft core, 5744 shell and 12967 cloud genes, highlighting the ‘close’ nature of P. rettgeri pan-genome. After a comprehensive pan-genome analysis, representative biological information has acquired that includes phylogenetic distances, presence or absence of genes across the P. rettgeri bacteria clade, and functional distribution of proteins. Moreover, pan-genome analysis has been shown to be an effective approach to better understand P. rettgeri bacteria because it helps developing various and tailored therapeutic strategies on the basis of their biological similarities and differences.